The first step to the unified world currency - Nefyodov, A. (KSU Publ., 2013)
It is specified that today the destiny of the main monetary unit of a planet excites all people of the world. It is noted that recently the dollar endures a difficult period of the existence. It is emphasized that in many countries, for leaving from risks of the American bank notes, started talking about need of creation of uniform national currency. It is described that the reason of crash of domination of the American dollar is existence in world economy of internal tendency to periodic financial and economic crises. The conclusion that extremely safe (evolutionary) version of the solution of problems of the world currency system testing today a stressful condition is necessary is drawn. The offer that the right of further issue of the American dollar to transfer to Economic and Social Council of the UN is made. Locates that transfer of a right of emission of dollar to special body of the UN for all countries of the world will bring definiteness in new world financial architecture.
Бірыңғай əлемдік валютаға алғашқы қадам
Первый шаг к единой мировой валюте
Keywords: prices; dollar; moreover; supranational currency; the reformatting; practice of impact; process; financial market; regional currencies; international management